Urban agriculture, racial capitalism, and resistance in the settler‐colonial city. Issue 6 (22nd May 2018) - McClintock, Nathan
Abstract: Recent scholarship on urban agriculture (UA)—the production of food in cities—argues that UA can both undergird and resist capitalist accumulation, albeit often at different spatio‐temporal scales. Scholarship that explicitly examines how UA, capitalist development, and racial difference work through one another, however, is less extensive. In this review, I propose that the lens of racial capitalism can elucidate UA's contradictory motivations and outcomes. As an analytical framework, racial capitalism considers how distinct forms of colonization, settler colonialism, and White supremacy function relationally as part of a unified system of capitalist accumulation built on the exploitation of racialized human and spatial difference. By focusing on UA's contributions to racial Othering, the racialization of space, and dispossession, on the one hand, and on struggles of resistance and self‐determination, on the other, this review attempts to sheds new light on the dialectical, "both/and" nature of UA, while also addressing recent calls to consider how settler colonial logics persist in the contemporary North American city.